A case of pulmonary cyst and pneumothorax after bronchial thermoplasty. Issue 2 (22nd December 2017) - Funatsu, Akifumi; Kobayashi, Konomi; Iikura, Motoyasu; Ishii, Satoru; Izumi, Shinyu; Sugiyama, Haruhito
Abstract : Bronchial thermoplasty (BT) is a bronchoscopic treatment for severe asthma using thermal energy to reduce smooth muscle in the bronchial wall. A 47‐year‐old man underwent BT for uncontrolled severe asthma despite maximal pharmacological treatment. After a third procedure, he experienced hypoxaemia because of complete bilateral upper lobe atelectasis. A pulmonary cyst suddenly emerged in to the right middle lobe, associated with the pneumothorax on postoperative day 6, and a chest drainage tube was inserted. As atelectasis of the right upper lung suddenly improved on postoperative day 12, pneumothorax and the cyst improved. Excess stress on the middle lobe due to upper lobe collapse, and check valve due to airway oedema and phlegm, might be related to pulmonary cyst formation. Tissue fragility related to systemic steroid usage and pressure load during pulmonary function testing might influence the occurrence of pneumothorax. Severe adverse events under complete atelectasis after BT require careful attention. Abstract : Bronchial thermoplasty (BT) is a bronchoscopic procedure for treating severe uncontrolled asthma using thermal energy to reduce airway smooth muscle. Previous studies have reported that BT improved asthma‐related quality of life and exacerbation of severe asthmatic patients. However, clinicians need to pay close attention as some unexpected severe complications of BT have been reported. We describe a case of pneumothorax preceded by pulmonary cyst development after BT.